Multidimensional Optical Control: Coherent Pixel Design of Metasurfaces for Multidimensional Optical Control of Multiple Printing‐Image Switching and Encoding (Adv. Funct. Mater. 51/2018). (17th December 2018) - Bao, Yanjun; Yu, Ying; Xu, Haofei; Lin, Qiaoling; Wang, Yin; Li, Juntao; Zhou, Zhang‐Kai; Wang, Xue‐Hua
Abstract : In article number1805306, Zhang‐Kai Zhou and co‐workers demonstrate a coherent pixel design for metasurface printing‐images, in which three optical parameters (i.e. incident wavelength, angle, and polarization) with arbitrary values can be simultaneously used to control image generation and switching. The coherent pixel design not only solves several problems of printing‐image switching, such as the cross‐talk among different wavelengths, but also allows promising applications in information encryption.